(untitled) (An Naba, 2020)
Imam Ghazali was an intelligent man and always prepared himself with the correct preparation of religion and consecrated his soul from the smudges of the flesh, so that he became a first-time phyosof Sufism prominent in his day. He doubts the truth of the heritage of ancestors where no one has disputed the truthfulness or digging the origins of customs.Al-Ghazali says, a person can only formulate an activity goal, if he understands correctly the underlying philosophy. This formulation of educational objectives will further determine the aspects of curriculum, methods, teachers and other related education. Al-Ghazali’s opinion on education is in line with religious shariah and ethics. Al-Ghazali did not forget worldly matters, so he did space in his educational system for worldly developments. In his view, preparing for the matter of the world was intended only as a pathway to the happiness of life in the more mainstream and eternal realms of the Hereafter. The world is a plantation tool for the Hereafter, as a tool that will lead one to meet his lord. It is of course for those who look at it as a place forever. From the results of the study of the thought of Al-Ghazali can be clearly known, that the final goal that is to be achieved through education activities there is 2, namely the first, the achievement of the Insani perfection that comes down to the approach of self to God. Secondly, the perfection of the Insani comes down to the happiness of the world and the hereafter. This purpose seemed religious and moral nuance, without neglecting worldly problems.